2023
DOI: 10.1002/cam4.5632
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of first‐line immunotherapies for advanced non‐small cell lung cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similar findings were also revealed in a meta-analysis enrolling 19 phase II/III RCTs in which the ABCP regimen was ranked 5 th among all 17 regimens including ABCP, 5 ICI-monotherapy regimens, 7 ICI-Chemo regimens, 2 dual-ICI strategies, 1 dual-ICI-Chemo combination, and 1 Beva-Chemo regimen, in which overall OS, PFS, safety, and ORR were taken into consideration ( 69 ). Furthermore, a cost-effectiveness analysis from the perspective of the US health care sector showed that adopting pembrolizumab monotherapy when PD-L1≥50%, pembrolizumab combined with chemotherapy when PD-L1 between 1%-49%, and nivolumab plus ipilimumab when PD-L1<1% were more cost-effective treatment options, whose performance was better than ABCP (QALY 2.39) ( 70 ). Similar results were revealed in several other cost-effectiveness analyses ( 71 ).…”
Section: Clinical Practices Of Anti-pd-1/pd-l1 Antibodies Plus Antian...mentioning
confidence: 99%
“…Similar findings were also revealed in a meta-analysis enrolling 19 phase II/III RCTs in which the ABCP regimen was ranked 5 th among all 17 regimens including ABCP, 5 ICI-monotherapy regimens, 7 ICI-Chemo regimens, 2 dual-ICI strategies, 1 dual-ICI-Chemo combination, and 1 Beva-Chemo regimen, in which overall OS, PFS, safety, and ORR were taken into consideration ( 69 ). Furthermore, a cost-effectiveness analysis from the perspective of the US health care sector showed that adopting pembrolizumab monotherapy when PD-L1≥50%, pembrolizumab combined with chemotherapy when PD-L1 between 1%-49%, and nivolumab plus ipilimumab when PD-L1<1% were more cost-effective treatment options, whose performance was better than ABCP (QALY 2.39) ( 70 ). Similar results were revealed in several other cost-effectiveness analyses ( 71 ).…”
Section: Clinical Practices Of Anti-pd-1/pd-l1 Antibodies Plus Antian...mentioning
confidence: 99%